Exploring the field of digital children’s literature and its opportunities for literacy education La letteratura digitale per l’infanzia e le opportunità per l’educazione alla lettura - Mascia Tiziana; Aerila Juli-Anna (La Scuola, 2026)
The importance of theoretically informed guidance for reading for pleasure with digital children's literature is likely to increase in the coming years as the digital reading landscape evolves and becomes more complex. Researchers, teachers, and readers interested in digital children's literature will need to consider multiple factors related to the use of technology and how they may influence the development and learning of children. In this article, we define the field of digital children's literature and explore its various formats. We employed a semi-structured literature review methodology to investigate the potential opportunities for literacy education, considering the impact on reading skills, interactivity and design, multimedia and transmedia storytelling, and mediated reading.
L'evoluzione e la complessità del panorama della lettura rendono sempre più necessaria un'approfondita conoscenza della letteratura digitale per l'infanzia. Ricercatori, insegnanti e lettori dovranno considerare molteplici fattori  legati all'uso della tecnologia e al loro impatto sull’ apprendimento dei bambini. In questo articolo, definiamo l'ambito della letteratura digitale per l'infanzia e le caratteristiche dei vari formati che essa include. Utilizzando una metodologia di revisione della letteratura semi-strutturata, esploriamo le opportunità per l’educazione alla lettura, valutando diverse prospettive: abilità di lettura, interattività e design dei libri digitali, racconto multimediale e transmediale e lettura mediata dalle nuove tecnologie.